2018
DOI: 10.1002/er.4233
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a solar tower power plant integrated with thermal energy storage system for cogeneration

Abstract: Summary In the current study, a solar tower–based energy system integrated with a thermal energy storage option is offered to supply both the electricity and freshwater through distillation and reverse osmosis technologies. A high‐temperature thermal energy storage subsystem using molten salt is considered for the effective and efficient operation of the integrated system. The molten salt is heated up to 565°C through passing the solar tower. The thermal energy storage tanks are designed to store heat up to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…They found that the suggested configuration is more effective than the use of PV panels and there is an increase in the electricity production of 20‐30%. Sorgulu and Dincer studied the use of solar heliostat for electricity and fresh‐water production. They found that the suggested configuration, which includes distillation and reverse osmosis units, is able to produce fresh‐water of 240 kg/s.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the suggested configuration is more effective than the use of PV panels and there is an increase in the electricity production of 20‐30%. Sorgulu and Dincer studied the use of solar heliostat for electricity and fresh‐water production. They found that the suggested configuration, which includes distillation and reverse osmosis units, is able to produce fresh‐water of 240 kg/s.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of short term ESS technologies include flywheel energy storage, battery ESS, superconducting magnetic energy storage, supercapacitor, and ultracapacitor energy storage . Depending on the storage medium, ESSs are categorised either as mechanical, chemical, or electrical storage systems . A survey of the literature shows that few studies have integrated ESS in GEP models …”
Section: Environmental Considerationsmentioning
confidence: 99%
“…The amount of available waste heat is the critical factor for the design of the desalination plant. Therefore, waste heat from other sources should be considered to increase desalination capacity, if necessary or a thermal energy storage unit can be incorporated for better management of waste heat source . Final condenser requires cold water to condense water vapor in the last effect, the performance of which depends on the seawater temperatures.…”
Section: Special Considerations and Future Perspectivesmentioning
confidence: 99%
“…On the other hand, the use of process waste heat and renewable or nuclear energy sources has been widely advocated for desalination industry because of the large quantities of thermal energy required by desalination processes . High‐temperature desalination processes are usually constructed in cogeneration schemes to enable combined water‐power production to improve overall economics and reduce environmental impacts.…”
Section: Introductionmentioning
confidence: 99%